2023
DOI: 10.1039/d2nj04763b
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into BCN nanomaterials – synthesis, properties and applications

Abstract: This review provides an overview of materials within B–C–N triangular zone. The structure, properties, synthesis routes and applications of boron carbon nitride (BCN) nanomaterials has been discussed in detail. Boron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 230 publications
(259 reference statements)
0
27
0
Order By: Relevance
“…30 Given the variable properties of such materials, BCN monolayers have been used in a wide range of applications, including gas sensors, catalysis, and energy storage. 32 Many BCN studies prioritized photocatalytic water splitting and other applications over developing and characterizing CO 2 reduction photocatalysis. 32 However, some researchers found that BCN monolayers showed a greater ability to absorb CO 2 than graphene.…”
Section: Introductionmentioning
confidence: 99%
“…30 Given the variable properties of such materials, BCN monolayers have been used in a wide range of applications, including gas sensors, catalysis, and energy storage. 32 Many BCN studies prioritized photocatalytic water splitting and other applications over developing and characterizing CO 2 reduction photocatalysis. 32 However, some researchers found that BCN monolayers showed a greater ability to absorb CO 2 than graphene.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Furthermore, the control of crystal structure, orientation, defects, and hydrogen and oxygen level in carbon nitride will also strongly influence hydrogen evolution performance. [43][44][45] Although several reviews pertaining to g-CN and their HER applications have previously been published, [23,[46][47][48][49][50][51][52][53][54][55][56][57][58] they were rather focused on materials or performance aspects, and no study comprehensively summarized the strategies to improve the performance of photocatalysis toward HER. In this work, we will introduce and discuss the strategy for improving the efficiency of photocatalysis-based water splitting, including bandgap and electronic structure engineering, heterostructure configuration, crystallinity control, structure and defects, and generating active sites by the incorporation of other catalysts and structural engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Although 2D metal-free materials such as zero-bandgap graphene and wide-bandgap h-BN have various potential applications, they are not ideal candidates as photocatalysts due to the lack of suitable bandgaps for water splitting. , On the other hand, 2D B x C y N z materials with bandgaps between graphene and h-BN can be synthesized through B- and N-doping of graphene or C-doping of h-BN. These 2D B x C y N z exhibit unique physical and chemical properties and show promise for applications in nanoelectronics and nanophotonics. However, only a few B x C y N z nanosheets, such as carbon doping of h-BN nanosheets, demonstrate potential for photocatalytic water splitting .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the square-octagon structure of twin T-graphene with outstanding dynamic and thermal stability has been reported. However, despite the successful fabrication of hexagonal BCN monolayers, , research on the square-octagon BCN monolayer is scarce. Our study draws inspiration from the unique atomic arrangement of twin T-graphene. , By substituting certain carbon atoms in twin T-graphene with nitrogen and boron atoms, we propose a square-octagon BCN 2D material that exhibits exceptional electronic, mechanical, and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation